What Historical Sources Say About Boysun? (Eurasian Journal of History, Geography and Economics, 2024)
In recent times, important scientific researches are being carried out to study the ethnogenesis and ethnic history of our people, to restore our material and spiritual heritage and to inculcate it in the minds of the young generation. The article presents an analysis of historical sources about the ancient history of Boysun, a district located in Surkhandarya region